AÇÃO INIBITÓRIA DE MICOCINAS SOBRE FUNGOS ANEMÓFILOS ISOLADOS DE UTI NEONATAL - Vieira, Jessica (2022)
Fungi can colonize different substrates and habitats. Atmospheric air is the most used and most successful dispersion environment for these organisms. Airborne fungi, with the ability to establish themselves and contaminate the air, reduce the life quality of the organisms that circulate there. Invasive fungal nosocomial infections have progressively emerged as a relevant source of morbidity and mortality in patients, especially the immunosuppressed patients. The broad spectrum of antimicrobial activity and the great stability led to the use of Wickerhamomyces anomalus as a biocontrol agent, since it could be classified as a low-risk microorganism. In addition, the antimicrobial action of mycocins produced from this yeast in eukaryotic and prokaryotic microorganisms is already proven. Based on this, the aim of the present study was to evaluate the inhibition of airborne fungi isolated in a Neonatal ICU by mycocins produced by W. anomalus. The mycocin containing W. anomalus culture supernatant showed β-glucanase activity of 4.2 U/mg. For fungal monitoring and inhibition test in solid environment, the passive sedimentation technique was used in Petri dishes exposed in the Neonatal ICU, for 15 minutes at 1 m high from the floor and away from the walls. The test consisted of a control plate containing Sabouraud Dextrose Agar, and another composed of culture medium and W. anomalus mycocin supernatant. Then, after incubation, the growth and/or inhibition of the collected fungi was observed. The growth of 15 genera was observed on the control plates: Aureobasidium spp., Curvularia spp., Emmonsia spp., Geotrichun spp., Fusarium spp., Rhizopus spp., Rhodotorula spp., Scedosporium spp., Chrysosporium spp., Trichoderma spp., Alternaria spp., Aspergillus spp., Acremonium spp., Penicillium spp. and Cladosporium spp. Cladosporium spp. was the most incident in the analyzed period, 40% (86 UFC). Meanwhile, on the test plates there was no growth of microorganisms. As a result, we can see the potential of W. anomalus mycocins in the development of new antimicrobial substances.